Effects of food combinations and stress on blood sugar dynamics - Chee, Samantha Suhui (Nanyang Technological University, 2022)
The increasing prevalence of Diabetes Mellitus (DM), globally and locally, prompts the look for interventions. Diet and stress are main factors for blood glucose level (BGL) spikes. Our gut health, which exhibits some form of relationship with our BGLs, is also affected by these factors. Hence, this project aims to empower individuals in making better lifestyle decisions related to their BGLs, food composition, stress, and gut microbiota. BGLs, heart rate (HR) and stress data were collected and processed from the author of this thesis. Food intake was quantified using an Artificial Intelligent (AI) system. It was found that while carbohydrates remain the biggest contributor to poor glycemic control, this can be countered with higher protein intake, with a higher protein-to-fats (P/F) ratio adopted. Smaller, more frequent meals may also help in controlling BGLs. Increasing both dietary fiber and sodium intake may also keep BGLs low, with dietary fiber-to-sodium (DF/S) ratio kept higher. Trans-fats intake should be minimal. Stress was found to cause larger and secondary BGL spikes. Lastly, with an animal-based diet, chicken or beef may be the more ideal protein sources for overall gut health. In conclusion, with an AI-based model, BGLs outcomes can be predicted and better managed.